2008
DOI: 10.1345/aph.1k565
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Dorzolamide – Timolol Alone or Combined with Latanoprost in Open-Angle Glaucoma or Ocular Hypertension

Abstract: In patients with primary open-angle glaucoma or ocular hypertension and elevated IOP while on monotherapy with latanoprost, switching to dorzolamide-timolol or combining dorzolamide-timolol with latanoprost are effective and safe treatment options for reducing IOP and achieving therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…We decided to use peak values (higher percentage POAG= primary open-angle glaucoma; FCTD= fixed combination of 0.5% timolol maleate/2% dorzolamide; NPDS= non penetrating deep sclerectomy of IOP reduction) for effectiveness. For the additive effect of FCTD over the prostaglandin analogue, only two studies were found in the literature and all of them evaluated the IOP reduction effect of FCTD added to latanoprost (20,21) . We assumed the same effect for the other two prostaglandin analogues (bimatoprost and travoprost).…”
Section: Methodsmentioning
confidence: 99%
“…We decided to use peak values (higher percentage POAG= primary open-angle glaucoma; FCTD= fixed combination of 0.5% timolol maleate/2% dorzolamide; NPDS= non penetrating deep sclerectomy of IOP reduction) for effectiveness. For the additive effect of FCTD over the prostaglandin analogue, only two studies were found in the literature and all of them evaluated the IOP reduction effect of FCTD added to latanoprost (20,21) . We assumed the same effect for the other two prostaglandin analogues (bimatoprost and travoprost).…”
Section: Methodsmentioning
confidence: 99%
“…Both fixed dorzolamide/timolol and fixed brimonidine/timolol effectively reduce IOP when used alone7,8,11 or adjunctively with a prostaglandin analog,28,34 the most common first-line therapy 35. Further, both fixed dorzolamide/timolol7,8 and fixed brimonidine/timolol11 reduce IOP more effectively than monotherapy with their component medications.…”
Section: Efficacy and Safety Of Fixed Combinations Compared With Compmentioning
confidence: 99%
“…Most clinical studies reported that triple non-fixed combination therapy of 2% dorzolamide, 0.5% timolol, and 0.002% latanoprost has a superior IOP lowering effect ( Akman et al, 2005 ; Lesk et al, 2008 ; Hatanaka et al, 2010 ; Konstas et al, 2017 ). Konstas AG, et al found that LTDz-nFC protects IOP from fluctuation and further more IOP reduction than latanoprost, DzT-FC, and LT-FC, with a mean 24 h-IOP of 22.1 mmHg, 19.9 mmHg, 19.5 mmHg, and 16.5 mmHg, and a IOP fluctuation of 4.7 mmHg, 4.4 mmHg, 4.1 mmHg, and 3.6 mmHg in latanoprost, DzT-FC, LT-FC, and LTDz-nFC-treated patients ( Konstas et al, 2017 ).…”
Section: Topical Non-fixed Combination Of Three Agentsmentioning
confidence: 99%